(untitled) - Hughes, Richard L. (Boston, 2006)
"Leadership: The Art of Experience, Fifth Edition", is written for the general student to serve as a stand-alone introduction to the subject of leadership. The text consists of 13 chapters and a final section on Basic and Advanced Leadership Skills. Authors Hughes, Ginnett, and Curphy have drawn upon three different types of literature: empirical studies; interesting anecdotes, stories and findings; and leadership skills to create a text that is personally relevant, interesting and scholarly. The authors' unique quest for a careful balancing act of leadership materials help students apply theory and research to their real-life experiences.
Keywords: Leadership